RPA-CRISPR/Cas12a mediated isothermal amplification for visual detection of Phytophthora sojae - Guo, Yufang; Xia, Hongming; Dai, Tingting; Liu, Tingli (Frontiers in Cellular and Infection Microbiology, 2023)
Phytophthora sojae is among the most devastating pathogens of soybean (Glycine max) and severely impacts soybean production in several countries. The resulting disease can be difficult to diagnose and other Phytophthora species can also infect soybean. Accurate diagnosis is important for management of the disease caused by P. sojae. In this study, recombinase polymerase amplification (RPA) in combination with the CRISPR/Cas12a system were used for detection of P. sojae. The assay was highly specific to P. sojae. The test results were positive for 29 isolates of P. sojae, but negative for 64 isolates of 29 Phytophthora species, 7 Phytopythium and Pythium species, 32 fungal species, and 2 Bursaphelenchus species. The method was highly sensitive, detecting as little as 10 pg.µL−1 of P. sojae genomic DNA at 37°C in 20 min. The test results were visible under UV light and readout coming from fluorophores. In addition, P. sojae was detected from natural inoculated hypocotyls of soybean seedlings using this novel assay. The rapidity and accuracy of the method were verified using 30 soybean rhizosphere samples. In conclusion, the RPA-CRISPR/Cas12a detection assay developed here is sensitive, efficient, and convenient, and has potential for further development as a kit for monitoring root rot of soybean in the field.